Financial balance of home nursing care providers in the Czech Republic - Fiala, Petr; Holmerova, Iva; Ruda, Tomas; Steffl, Michal (Health economics review, 2021)
BACKGROUND: To enable people to live in old age in their own homes often requires specialised home care services. Despite the high importance of these services, the finance of home nursing care (HNC) is still under-investigated in many countries. The aim of this paper was to describe the finance of HNC in the Czech Republic. METHODS: Balancing of revenues and costs was done using structured questionnaires from the closed accounting year 2018 as a monthly average. Nonparametric Kruskal-Wallis and Wilcoxon signed ranks tests were used to test hypotheses. RESULTS: Data from 62 providers were analysed. The data included information from a total of 2297 patients and 995 employees. The average of total costs were € 17,591.7 (95% CI 14,175.3 - 21,008.1) and average of total revenues were € 17,276.5 (95% CI 13,923.5 - 20,629.5). The average cost per a patient was € 516.0 (95% CI 465.9-566.1) and the average revenues were € 500.1 (95% CI 457.0-543.3). CONCLUSIONS: The overall financial balance of HNC providers seems to be balanced in the Czech Republic. Nevertheless, insurance, although it should, did not cover all the costs. Micro- providers tended to be cheaper regarding the hours worked by nurses.
Keywords: Indirect costs; Direct costs; Home care services; Long-term care